Analisis Pemahaman Calon Guru IPA dalam Menyususun Modul Ajar (Proyek Penguatan Profil Pelajar Pancasila) pada Kurikulum Merdeka - Nurhayati Nurhayati; Nur Mustaqimah; Nurul Fajryani Usman; Munawwarah Munawwarah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to analyze the ability of prospective science teachers to compile teaching modules. The method of this research is descriptive-qualitative. This research is based on a post-positivist understanding that has a naturalistic nature. The technique used by researchers in determining research subjects is purposive sampling. The subjects in the research were prospective science teachers, namely 6th semester science education students in the class of 2020. These students were students who had taken the science teaching planning course. The number of research subjects was 25. The research period is from April to July 2023. The research instruments are interviews, observation sheets, and documentation. The research process takes place in three steps, namely (1) preparation. The preparation process includes observation, identifying data sources, preparing a research instrument, and validating an instrument that has been created. (2) Implementation stage, in conducting research on student document reviews. This study examines the teaching modules created based on the curriculum in full. This research uses an approach in the form of content analysis. (3) At the data analysis stage, all documents that have been collected will then be analyzed and conclusions drawn. The results of the research are that the ability to prepare independent curriculum teaching modules for prospective science teachers from three aspects (general information, core components and attachments) is categorized as good and in accordance with the independent curriculum.